Incidencias tributarias en una empresa comercial SAC - 2019 - Muñoz Noriega, Larry Alvaro (2022)
In this thesis I obtain a favorable result that the companies are corporate, legal or natural persons with businesses comply with paying their taxes monthly, therefore the Tax Incidences in a Commercial Company SAC-2019, this research is of Qualitative- Descriptive type, its study population was 25 people, employees entrepreneurs of this category. As a conclusion we have a 64% of efficient, that the companies in our country, comply with the mandatory payment of their taxes on a monthly and annual basis, also has a 08% of informality, because there is a sector of companies that work informally, that do not pay any taxes for years. Informality is a damage that is done to the country, these companies that work informally obtain significant profits, but do not contribute with any tax to the state, therefore the government should implement measures, to welcome these informals, with the objective of increasing the tax collection, and develop the country.